The Legislative Approach to Employer Liability in Workplace Sexual Harassment Within the PRC Legal Framework: Taking American as a Counterpart - Fan, Chiyu (Transactions on Social Science, Education and Humanities Research, 2024)
Workplace sexual harassment is a prominent issue across the globe, despite a late start, China has made huge progress in legislation in recent years. However, China’s personality approach is insufficient in both legislation and judicial practice, especially the underemphasis on employer’s liability. Some studies are addressing this issue, but the cause of this problem remains understudied. Thus this article attempts to fill in the missing parts of the discussion. Firstly by reviewing the legislative progress, this article emphasizes the interplay between domestic values and international legislative influences. Then discusses the practical challenges in judicial practice, including the underemphasis on employer liability and the need for clearer guidelines on accountability. By re-examining the collective movement and women’s liberation movement after 1949, This article argues that the avoidance of addressing sexual harassment in the public sphere and the neglect of employer responsibility are deeply rooted in our history. Then by comparing the social movement and legislative approach with the U.S., this paper argues that: (i) adopting the sex discrimination model and (ii) encouraging community engagement by forming a bottom-to-top movement would be beneficial to future legislation and judicial practices concerning workplace sexual harassment. Mass culture and societal currents are crucial for China to emphasize the employer’s liability both in legislation and judicial practice.